2013
DOI: 10.1371/journal.pone.0080447
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stress Impairs Mitosis Progression in Multi-Cellular Tumor Spheroids

Abstract: Growing solid tumors are subjected to mechanical stress that influences their growth rate and development. However, little is known about its effects on tumor cell biology. To explore this issue, we investigated the impact of mechanical confinement on cell proliferation in MultiCellular Tumor Spheroids (MCTS), a 3D culture model that recapitulates the microenvironment, proliferative gradient, and cell-cell interactions of a tumor. Dedicated polydimethylsiloxane (PDMS) microdevices were designed to spatially re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 35 publications
(38 reference statements)
5
65
0
2
Order By: Relevance
“…Therefore, we speculated that a percolation cluster with a different occupation probability should be suitable for describing the proliferation and spread of a tumor in an inhomogeneous surrounding matrix, which itself should be compressive to tumor proliferation and invasion. The results are basically in accordance with previous studies that showed that the surrounding matrix possesses a specific external pressure on a solid tumor [42][43][44]70]. …”
Section: Influence Of Tissue Inhomogeneity On Tumor Proliferation Andsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, we speculated that a percolation cluster with a different occupation probability should be suitable for describing the proliferation and spread of a tumor in an inhomogeneous surrounding matrix, which itself should be compressive to tumor proliferation and invasion. The results are basically in accordance with previous studies that showed that the surrounding matrix possesses a specific external pressure on a solid tumor [42][43][44]70]. …”
Section: Influence Of Tissue Inhomogeneity On Tumor Proliferation Andsupporting
confidence: 92%
“…This finding can be interpreted to mean that tumor cells are hampered by the sparse distribution of the surrounding matrix on an inhomogeneous percolation cluster and their further diffusion and migration are scarce when the occupation probability P is sufficiently low. The results are in accordance with research by Cheng et al [43] and Desmaison et al [44], showing that inhomogeneity in the mechanical properties of a confining environment could affect tumor cells distribution and morphology by inducing apoptosis.…”
Section: Comparison Of Several Lattice Constructorssupporting
confidence: 92%
See 1 more Smart Citation
“…Studies of multicellular spheroids indicate that the mechanical pressure of the tissue environment can impair cell proliferation (33,34). Moreover, it has been predicted that cells in stiffer or more densely packed tissue environments, such as of an overgrown tumor, would require a more robust cell cortex and mitotic rounding response (9,35).…”
Section: Discussionmentioning
confidence: 99%
“…Cells that can survive in the absence of oxygen are therefore at a growth advantage compared to cells that cannot. Therefore, MCS, which mimic in vivo tumors with proliferative cells in the periphery and hypoxic centers (27), were used to evaluate hypoxia in vitro. When SCC9β6KDFyn cells were placed under hypoxic conditions a variety of changes occurred such as a 3-fold decrease in FN expression and a 2.5-fold decrease in Ncadherin expression (Figure 4).…”
Section: Discussionmentioning
confidence: 99%